Recent advances in the pathogenesis of acute kidney injury caused by COVID-19 - Wei Kai-yue; Mi Yan; Wang Cai-li (Linchuang shenzangbing zazhi)
Severe acute respiratory syndrome coronavirus 2 （SARS-CoV-2） is a highly contagious respiratory virus. Acute kidney injury （AKI） associated with COVID-19 （coronavirus disease 2019） has been reported in a growing number of clinical cases. Some recent studies noted that kidney might be a major target organ of SARS-COV-2. Multiple factors cause the changes of renal function， including direct viral toxicity， renin-angiotensin aldosterone system imbalances， disorders of immune system， cytokine storm， rhabdomyolysis， blood coagulation dysfunction， sepsis， drug-related renal toxicity and crosstalking between organ and symptoms caused by prerenal factors. This review summarized the potential pathogenesis of COVID-19-induced AKI.